Scaling community-based aquaculture for enhanced nutrition and women’s empowerment: lessons from Odisha, India - Dubey, Sourabh Kumar; Padiyar, Arun; Chadag, Vishnumurthy Mohan; Shenoy, Neetha; Gaikwad, Amar Bharat; Ratha, Baishnaba Charan; Belton, Ben (Frontiers Media, 2024)
Introduction: Aquatic foods, particularly fish, are essential for addressing malnutrition, especially in vulnerable populations like children and women. In India, traditional aquaculture practices centered around carp species often overlooked the production of nutrient-rich small fish. To address this, nutrition-sensitive aquaculture approaches advocate for integrating species like mola carplet (Amblypharyngodon mola) rich in micronutrients, into existing systems. In Odisha, India, where poverty and food insecurity are prevalent, the government initiated a program to empower women through aquaculture, focusing on nutrition-sensitive carp-mola polyculture in community ponds through Women Self-Help Groups (WSHGs).